Estudo comparativo entre o International Baccalaureate e o referencial curricular para o ensino médio do Paraná - Domingos, Fernando Kolb (2022)
This study aims to describe the existing connections between the Mathematics Curriculum of Paraná High School, according to the Referencial Curricular para o Ensino Médio do Paraná – RCEMP (PARANÁ, 2021) and the and the Mathematics Curriculum of the International Baccalaureate – IB (IB, 2019). To this end, the principles that underlie the mathematics curriculum used in international schools were described, that follow the guidelines of the International Baccalaureate Diploma Programme – IBDP, and the curricular guidelines that underlie the Referencial Curricular para o Ensino Médio, the Base Nacional Comum Curricular – BNCC. For the development of the work, the methodology of a bibliographic survey was used, using both curricula as guides. As main results, after analyzing the two curricula, it was found that there are some similarities, or connections, between the curricula, such as: the emphasis given to mathematical skills that students must develop throughout along the way; a concern with the use of technologies for teaching and learning; the relationship between Itinerários Formativos and the Subject Groups (IB); and also some content with the aim of preparing the student to continue their studies, although in quite different ways.